Molecular characterization of extended spectrum beta lactamase producing bacterial strains isolated from diarrheal patients. - Neupane,Bibhusan (2016)
ABSTRACT: Infectious diarrheal diseases are responsible for considerable morbidity and mortality especially in developing countries. Multidrug resistant organism and extended spectrum beta lactamase producing organism are growing problem in the treatment of infections. So the present study was carried out to detect the multidrug resistant organism and Extended spectrum beta lactamase producing organism isolated from patients suffering from diarrhea and visited Sukrraj Tropical and Infectious Disease. Hospital for treatment from mid-June 2014 to mid-December 2014. 624 stool specimens were collected from patients and cultured by standard microbiological technique. Isolated bacteria were identified by biochemical test and serotyping. These bacterial strains were subjected for Antibiotic susceptibility testing following Kirby Bauer disk diffusion technique as per CLSI guideline. ESBL producing strains were screened by disk diffusion and disk combination method. Phenotypic detected ESBL producing organisms were subjected for molecular characterization. Among culture positivity of stool culture, Vibrio cholera, salmonella and Shigella species were detected . 31 were Shigella species among them 17 were Shigella flexneri, 8 were Shigella sonnei, and 2 were Shigella dysenteriae, I was Shigella boydii and 3 were Shigella species which were biochemically confirmed, 22 were Vibrio cholera and 7 were Salmonella enteric serovar Typhimurium. Most Shigella were resistant to antibiotic, most of them were highly resistant to Nalixidic Acid, Ciprofloxacin, Ampicillin and Cotrimoxazole while more resistant to Vibrio Cholerae but Cefotaxime, Tetracycline and Ciprofloxacinwere more susceptible. One isolates among Salmonella enteric serovar Typhimurium was multidrug resistant while other were susceptible to antibiotics. One isolates each from Shigella flexneri, Vibrio cholera and Salmonella enteric serovar Typhimurium were ESBL producerin phenotypic detection. Vibrio Cholerae and Salmonella enteric serovar Typhimurium possess CTX-M gene indicating the threats of ESBL producing bacteria. Key Words: AST, CTX, Diarrhea, Vibrio Cholerae, Shigella , Salmonella